Advances in Lead-Free Perovskite Single Crystals: Fundamentals and Applications - Tailor, Naveen Kumar; Kar, Shaoni; Mishra, Pranjal; These, Albert; Kupfer, Christian; Hu, Hanlin; Awais, Muhammad; Saidaminov, Makhsud; Dar, M. Ibrahim; Brabec, Christoph; Satapathi, Soumitra (ACS Materials Letters, 2021)
With rapid progress in the deployment of metal halide perovskites in various device applications such as solar cells, light-emitting devices, field-effect transistors, photodetectors, etc., the next eminent focus is on the single crystals of these materials. With a lack of grain boundaries and low trap densities, remarkably long charge carrier diffusion lengths, and high ambient and operational stabilities, this class of materials seems greatly promising. Yet, the growing concern for lead toxicity in commercial semiconductor devices has entailed a thrust in the research of alternative lead-free perovskites, including their single crystalline forms. However, there is still no consolidated account of the state-of-the-art in this domain and accordingly, countless feasible systems still remain unexplored. To bridge this gap, we attempt to provide here, an up-to-date overview of lead-free perovskite single crystals with respect to their synthesis methods, structural diversity, stability, photophysical and electrical properties, and device applications. We discuss various approaches to designing, modeling, fabricating, and characterizing new single-crystal systems and conclude with some critical insights for further investigating this field of research.
CRIS-Team Scopus Importer:2021-07-16